UNION BUDGET 2016-17: GREAT EXPECTATIONS - PANDEY, DR. TARKESHWAR (IJRDO - Journal of Business Management, 2016)
The biggest expectation from Budget 2016-17 is the redressal of a plethora of issues – both pending and half-addressed – that await a tangible solution. A discernible outlining of goals, hopefully backed by an action plan, is likely to be the theme for this year’s budget. On the face of it, the NDA government seems determined to resolve a host of key issues: upliftment of the rural sector, mitigation of adverse weather effects on agriculture, creation of more employment opportunities, and enriching the lives of women, children, senior citizens and people below the poverty line. 2. The Union Budget 2015: As an event, was hyped way too much, so to speak. Understandably so, given that it happened to be the first budget of the Modi government. A look back on the government initiatives till date boils down to several observations. Issues like alleviating taxation woes and GST are yet to be taken care of. But, in all fairness, measures like inviting Foreign Direct Investment (FDI) in railways and defense, insurance legislation, labor reforms and the nod to defense deals and infrastructure projects and deregulation of diesel prices bear testimony to PM’s intentions to bolster an all-encompassing growth and development of India. Modi has vowed to wipe out tax terrorism from India. Hopes of GST getting the green signal in the upcoming Parliament session have started to glimmer. However, persistent opposition in the Rajya Sabha till date has been a  dampener. India’s growth story has its eyes set on April 1, 2016, which is the GST roll out deadline set by the government, given the hope that it will iron out the wrinkles in the current system of taxation.